2017
DOI: 10.1111/jpn.12766
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus plantarum BS22 promotes gut microbial homeostasis in broiler chickens exposed to aflatoxin B1

Abstract: SummaryProbiotics promote the health of the host by maintaining intestinal microbial homeostasis. This study aimed to investigate the benefits of Lactobacillus plantarum BS22 (LP) in the gastrointestinal tract (GIT) microbial homeostasis of broiler chickens exposed to aflatoxin B 1 using the PCR-DGGE, viable count and real-time PCR. The toxin adsorption experiment demonstrated that treatment R5 (1.0 × 10 8 CFU/g LP) exhibited good absorptive effect in adsorbing the aflatoxin B 1 (AFB 1 ) in vitro. DGGE show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…These findings indicate that the microbial colonization of the gastrointestinal tract gradually changes until a mature and complex microbial community is established ( Babot et al., 2014 ). Several other studies have demonstrated that Lactobacillus could be potential to prevent the colonization of pathogens, promote intestinal health, and improve growth ( Jones and Versalovic, 2009 ; Zeng et al., 2017 ). The Spearman analyses further showed that the Lactobacillus was positively correlated with the VH and VH:CD in the ileum of the growing broilers.…”
Section: Discussionmentioning
confidence: 99%
“…These findings indicate that the microbial colonization of the gastrointestinal tract gradually changes until a mature and complex microbial community is established ( Babot et al., 2014 ). Several other studies have demonstrated that Lactobacillus could be potential to prevent the colonization of pathogens, promote intestinal health, and improve growth ( Jones and Versalovic, 2009 ; Zeng et al., 2017 ). The Spearman analyses further showed that the Lactobacillus was positively correlated with the VH and VH:CD in the ileum of the growing broilers.…”
Section: Discussionmentioning
confidence: 99%
“…L. plantarum strains from different food sources have been reported for their ability to control A. flavus and aflatoxins. L. plantarum strains possess the ability to reduce the toxicity of aflatoxins through binding activities or promoting gut microbial homeostasis in broiler chickens exposed to aflatoxin B 1 [21,22,23]. In our current study, strain IAMU80070 was isolated from kimchi and characterized.…”
Section: Discussionmentioning
confidence: 99%
“…The perinatal and neonatal GIT is more sensitive to bacteria, as these intestinal cells have increased plasticity to reprogram the transcriptional and proteomic profile, which may predispose the host to disease or improved performance into adult life ( Cortese et al., 2016 ). Knowledge about the role of commensal Enterobacteriaceae found in chicks is generally limited, beyond their role as pathogens ( Crhanova et al., 2011 , Awad et al., 2016 , Zeng et al., 2018 ). The in ovo technique applied here may allow for the control of pioneer colonization and to influence the GIT development based on the pioneering microbiota in the host.…”
Section: Discussionmentioning
confidence: 99%